ANALYSIS OF FINANCIAL REPORTS TO ASSESS FINANCIAL PERFORMANCE AT PT. XXX Tbk - Muhammad Azhari; Yosep Sanga Liwun (Universitas Maarif Hasyim Latif, 2022)
This study aims to determine financial performance by analyzing the financial statements of PT. Unilever Tbk, listed on the Indonesia Stock Exchange (IDX) for 2017-2021. The data used in this study comes from the company's financial statements in the form of balance sheets and income statements of PT. Unilever Tbk for the period 2017- 2021 using descriptive quantitative research methods. By using the components of financial performance, in this case, related to the ratio of liquidity, profitability, solvency and activity ratios. From the results of the calculation of the financial values of PT. Unilever Tbk shows that the ratios that have met the standards or the ratios are considered good are the solvency ratio, namely the debt to equity ratio; the profitability ratio, namely the return on investment and return on equity; and the ratio activity, namely the ratio of total assets turn over. While the value of the ratio considered not good or the ratio number does not meet industry standards is the Liquidity ratio, namely the current ratio and the quick ratio; solvency is the debt to assets ratio, and activity is the fixed assets turnover ratio.